Examining the Mediating Role of Strategic Integration of Purchasing, And Advance Purchasing Practices in the Relationship between Purchasing Operational Performance and IT Investment in Purchasing - GholamReza Zandi; Dewan Md. Zahurul Islam; Nadeem Khalid (International Journal of Supply Chain Management, 2019)
The main purpose of the current study is to investigate the mediating role of strategic integration of purchasing, and advance purchasing practices in the relationship between purchasing operational performance and IT investment in purchasing. In this research, some other practices have been considered including involvement of suppliers, evaluation and assessment of suppliers and integration of logistics. Strategic integration of purchasing is referred as the degree to which the strategic relevance of purchasing function is recognized by a company. This has been regarded as an important antecedent of supply management practices and advanced purchasing. In the relation of performance, supply and purchasing practices and IT investments, one of the important factors is strategic integration of purchasing. The study has used survey-based method and data is collected by the aid of questionnaire. The collected data is analyzed with the SEM-PLS. The findings of the study have shown agreement with the proposed results. In author knowledge it is among the pioneering studies on the issues related to strategic integration of purchasing, advance purchasing practices, purchasing operational performance and IT investment in purchasing. This study will provide guidelines to policymakers, researchers and corporate personnel in understanding the relationship between strategic integration of purchasing, advance purchasing practices, purchasing operational performance and IT investment in purchasing.